Extreme music for extreme people? Norwegian black metal and transcendent violence - Phillipov, Michelle (Popular Music History, 2012)
This article focuses on the events of the Norwegian black metal scene in the early 1990s, a period in which violent aesthetics in metal music became explicitly and deliberately articulated to real acts of violence. Concentrating on the musical and criminal activities of the band Emperor, the author suggests that the group’s success was, at least in part, the result of members’ simultaneous promotion and disavowal of their involvement in violent crime. The case highlights not only how not all claims of a link between music and violence are entirely fabricated, but also the necessity of rethinking conventional approaches to music, violence and controversy, given the ongoing legacy of the events of the early 1990s within the contemporary black metal scene.